Adams family papers - Adams, Abigail, 1744-1818.; Adams, Charles Francis, 1807-1886.; Adams, Charles Francis, 1835-1915.; Adams, Henry, 1838-1918.; Adams, John, 1735-1826.; Adams, John Quincy, 1767-1848.; Adams, Louisa Catherine, 1775-1852.; Adams, Samuel, 1722-1803.
Chiefly correspondence of John Quincy Adams. Also includes correspondence and other papers of Abigail Adams, Charles Francis Adams (1807-1886), Charles Francis Adams (1835-1915), Henry Adams, John Adams, Louisa Catherine Adams, Samuel Adams. Includes Henry Adams' address to the American Historical Association in a letter dated 1894 to Herbert B. Adams. Documents social life in Massachusetts and state and national political affairs. Correspondents include Joseph Blunt, Alexander Hill Everett, Thomas Jefferson, James Madison, and Robert Welsh, Jr.
In part, transcripts and negative photocopies.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Herbert Baxter, -- 1850-1901 -- Correspondence; Blunt, Joseph, -- 1792-1860 -- Correspondence; Everett, Alexander Hill, -- 1790-1847 -- Correspondence; Jefferson, Thomas -- 1743-1826 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Welsh, Robert -- Correspondence; Adams family; American Historical Association; Massachusetts -- Politics and government; Massachusetts -- Social life and customs; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1865.; Authors; Cabinet officers; Diplomats; Historians; Presidents -- United States; Presidents' spouses -- United States; Representatives, U.S. Congress -- Massachusetts; Vice-Presidents -- United States